2017
DOI: 10.1093/nar/gkx912
|View full text |Cite
|
Sign up to set email alerts
|

The RNA binding protein EWS is broadly involved in the regulation of pri-miRNA processing in mammalian cells

Abstract: The Ewing Sarcoma protein (EWS) is a multifaceted RNA binding protein (RBP) with established roles in transcription, pre-mRNA processing and DNA damage response. By generating high quality EWS–RNA interactome, we uncovered its specific and prevalent interaction with a large subset of primary microRNAs (pri-miRNAs) in mammalian cells. Knockdown of EWS reduced, whereas overexpression enhanced, the expression of its target miRNAs. Biochemical analysis revealed that multiple elements in target pri-miRNAs, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…More recently, studies have revealed that lncRNA can regulate the expression of key gene at various levels, such as epigenetic modification, transcription, and posttranscription, through a variety of mechanisms such as RNA‐RNA, RNA‐protein, and RNA‐DNA . Accumulating evidence has suggested that lncRNA binds to miRNAs in a competitive manner as a competitive endogenous RNA (ceRNA) to regulate gene expression, which is an important molecular mechanism of lncRNA involved in regulating the occurrence and development of diseases . Recent studies have demonstrated that specific lncRNAs share a close correlation with neural cell differentiation, synapses, elevated neuronal excitability, and neural network connection and remodeling, all of which suggest their possible involvement in the occurrence and development of epilepsy …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, studies have revealed that lncRNA can regulate the expression of key gene at various levels, such as epigenetic modification, transcription, and posttranscription, through a variety of mechanisms such as RNA‐RNA, RNA‐protein, and RNA‐DNA . Accumulating evidence has suggested that lncRNA binds to miRNAs in a competitive manner as a competitive endogenous RNA (ceRNA) to regulate gene expression, which is an important molecular mechanism of lncRNA involved in regulating the occurrence and development of diseases . Recent studies have demonstrated that specific lncRNAs share a close correlation with neural cell differentiation, synapses, elevated neuronal excitability, and neural network connection and remodeling, all of which suggest their possible involvement in the occurrence and development of epilepsy …”
Section: Introductionmentioning
confidence: 99%
“…7 Accumulating evidence has suggested that lncRNA binds to miRNAs in a competitive manner as a competitive endogenous RNA (ceRNA) to regulate gene expression, which is an important molecular mechanism of lncRNA involved in regulating the occurrence and development of diseases. 8,9 Recent studies have demonstrated that specific lncRNAs share a close correlation with neural cell differentiation, synapses, elevated neuronal excitability, and neural network connection and remodeling, all of which suggest their possible involvement in the occurrence and development of epilepsy. [10][11][12][13] MiRNAs represent a class of endogenous ncRNA encoded by the genome of higher eukaryotes with a length of about 22 nt.…”
Section: Introductionmentioning
confidence: 99%
“…The role for NEAT1_1 in this process is less clear, however, it may potentiate NEAT1_2 function. A number of NEAT1-binding proteins, namely FUS, TDP-43, SFPQ and EWS, have been reported to modulate miRNA biogenesis [ [95] , [96] , [97] , [98] ].…”
Section: Neat1/paraspeckles Regulate Cellular Pathways Commonly Affecmentioning
confidence: 99%
“…Finally, our resource has also registered biomarkers like EWS, Cit-H3, and ACE2, that have extensive ramifications in various cancers. EWS, primarily implicated in Ewing’s Sarcoma, plays a role in transcriptional repression, and promotes tumorigenesis by forming fusion proteins 72 , 73 . Cit-H3 plays an important role in neutrophil release of nuclear chromatin, also called neutrophil extracellular traps (NETs), which have been associated with tumor progression in colon cancer 74 , 75 .…”
Section: Resultsmentioning
confidence: 99%